HUBUNGAN PENGETAHUAN PERTOLONGAN PERTAMA DENGAN MOTIVASI MENOLONG KORBAN KECELAKAAN LALU LINTAS PADA MASYARAKAT DI JALAN PROF. DR. IDA BAGUS MANTRA, BALI - Putu Gede Putra Suastrawan; I Kadek Saputra; Ni Putu Emy Darma Yanti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
One of the incidents that became a global health problem that caused many disasters was a traffic accident. This incident proved to have resulted in many victims and losses. As a first responder, people need to have first aid knowledge and motivation to help victims of accidents to reduce these losses. Traffic accident mortality rates can be reduced by 85% with good knowledge and help. The purpose of this study was to identify the relationship between first aid knowledge and motivation to help victims of traffic accidents to the community on Jalan Prof. Dr. Ida Bagus Mantra, Bali. This research is a quantitative, correlative descriptive design with a cross-sectional approach. The sample used was 106 people with the selection of purposive sampling techniques. Relationship analysis using the Spearman test. The results of this study found a relationship between first aid knowledge with helping motivation and the strength of a moderate relationship. Researchers recommend to the community to take first aid training so that it increases motivation to help.